CONSORTIUM OF FISHERY INSTITUTE LIBRARIES IN KERALA: A PROPOSAL - Ancy Jacob and S.Ally Sornam
Many of the fisheries institutes in Kerala are in their infancy and they do not have self-radiant library and information system to assist their teaching as well as learning process. Only a few colleges have good information centre and resources. Self- sufficiency remains only imaginative, because of insufficient funds and information explosion. The sky rocketing cost of periodicals and books in every discipline and even the richest libraries cannot afford to subscribe to all of them, to fulfill the user demands and inflation impelled libraries towards resource sharing. For effective functioning of sharing of information sources, a realistic approach has to be worked out in collection development, networking, etc and taking into consideration the present information, communication and computing infrastructure as well as psychosocial aspects of fisheries manpower and users. The study aims to develop a library consortium for the Fisheries institutes in Kerala. At present, there is no such consortium, and an initiation for it would mutually benefit for all the participating institutions. The proposed study will also add values to the existing information infrastructure of the technical education in Kerala.